Gunung Merapi Dalam Budaya Jawa - Sumadi Sumadi (Ornamen, 2004)
For Javanese, Merapi Mountain isÂ believed asÂ the place of their anchestor spirit, gods, and spirit. It is also believed as the place of ghost or spirit such as in Jogyakarta Palace. Merapi Mountain is also believed as the strong character and strong soul, as the anger and generous god. The myth of holly agreement between the pioneer of Mataram dinasty and Sapu Jagad (Merapi Master) andÂ RoroÂ Kidul (The Queen of South Sea). The myth raises a concept of â€œsedulur papa lima pancerâ€, itâ€™s about the myth of geographic (The Palace, Merapi MounÂtain and Sout Sea) and the location of the spirit of the death person. Merapi Mountain and its concept often been used as the inspiration of monumental creation in Javanese art and culture.Keyword : gunungan, mitos, merapiÂ